Transitioning to L1 Instruction University: A Case Study of EMI Graduates in Indonesia - Hutabarat, Pritz (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
The phenomenon of English as a medium of instruction (EMI) has spread across the globe with the promise of equipping students with high English proficiency levels. While a plethora of research has been done to explore students’ and teachers’ readiness for EMI, very few have dealt with the reverse phenomenon, EMI graduates transferring from English to first-language (L1) medium instruction. Therefore, conducted as a case study of six EMI graduates, this research project seeks to understand how the participant adapted to L1 instruction at higher education. The data was collected using semi-structured interviews and analyzed using thematic analysis. The findings reveal seven themes in the participants’ experiences namely, developing critical thinking skills, reading skills and the love of literature, language flexibility, challenges in transitioning to L1 instructions, essay writing challenges, challenges in socializing, and mentoring and tutoring as a learning strategy. The study concludes that the participants had a positive experience transitioning from EMI to L1 instruction. They also value English as their linguistic capital and employ various strategies to make the transitioning process go smoothly. This study helps EMI teachers, parents, and policymaker to mitigate the transition process for students who are moving from one language of instruction to another. Such mitigation is necessary to reduce anxiety and improve student’s readiness to study in the new linguistic environment.